Control integrated studies on high speed permanent magnetic generators system - Li, Jing; Zhang, Xiaochen; Zhang, He; Huang, Xiaoyan; Gerada, C.; Galea, Michael (IEEE, 2015)
The power converter and its control system has great impact on the behavior of the high speed permanent magnet generator system (HSPGS) due to the high operating frequency, and therefore should be investigated in the design and research on the HSPGS. This paper investigates a 3kW 80,000 rpm HSPGS with the control system and evaluates machine performance. A study model composed of three dimensional finite element analyses and control system is proposed, and the magnetic density distribution in machine is investigated via FEA and power converter control directly coupled research. From the comparisons of simulation results of generator operating with or without control system, the effects of control system current time harmonics on the three dimensional flux distribution, the vector eddy current in rotor sleeve, and the iron loss of the machine are explored. By using the harmonics analyses, both the space flux harmonics and the voltage current time harmonics are obtained. The tested waveforms and voltage and current value of machine under different working conditions verify the calculated results. The obtained results could provide reference for system level design and investigation for HSPGS.